Successful pregnancy outcome in uncorrected tetralogy of Fallot with bidirectional shunt - Tauro, Sheral Raina; Devi, Rajkumari Praneshwari; Sen, Sayan; Rout, Anupam; Nayak, Archana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Tetralogy of Fallot (TOF), a cyanotic congenital heart disease, is the most prevalent type, constituting 10% of all congenital heart conditions. During pregnancy and childbirth, patients with uncorrected TOF can experience deterioration, posing a significant risk to maternal health and even mortality. A 30 year old patient was referred from a private clinic in view of uncorrected TOF in the third trimester of pregnancy. She was G3P1A1 who reported at 37 weeks 2 days period of gestation to the emergency room with history of breathlessness on routine activities for 10 days (NYHA III) and easy fatigability for 4-5 months and pain abdomen. Her previous antenatal and pre pregnancy period was uneventful with no history of cyanotic spells, dyspnea or palpitations. Electrocardiography showed sinus rhythm, right atrial enlargement, right ventricular hypertrophy with sudden transition of QRS in V2. Her echocardiography confirmed the findings of TOF. It revealed a large peri membranous VSD with bidirectional shunt with 50% overriding of aorta. There was non dysplastic severe pulmonary stenosis, right ventricular outflow tract narrowing with right ventricular hypertrophy, severe pulmonary hypertension, with a left ventricular ejection fraction of 56%. She underwent emergency cesarean section under general anesthesia in joint consultation of the obstetrics unit along with anesthesiologist, cardiologist, intensivist and neonatologist. Her cardiovascular status was never compromised. She was started on torsemide and was discharged on 6th post-operative day. She followed up with cardiologist after 4 weeks postpartum for further management.